Generation of a non-integrated induced pluripotent stem cell line from urine cells of a Chinese osteogenesis imperfecta type I patient - Jing Luan; Yazhou Cui; Jing Wang; Yanchen Liang; Yanan Zhao; Genglin Zhang; Jinxiang Han (Stem Cell Research, 2022)
Osteogenesis imperfecta (OI) is a group of genetic disorders characterized mainly by fractures and bone deformities. It has been established that gene mutations, particularly those in COL1A1 and COL1A2, account for most phenotypes. Here, we generated an induced pluripotent stem cells (iPSCs) line named SMBCi014-A using urine cells (UCs) derived from a 15-year-old female OI type I patient who carried the frame-shift mutation of the COL1A1 gene (exon35:c.2450delC:p.P817fs). The patient had a family history of mild fractures and a blue sclera. Therefore, our study established a patient-derived site-specific cellular model of OI to better understand the osteogenic mechanism.